Empowerment of Educational Tourism Pakusari Final Waste Disposal Site, Kertosari Sub-District, Pakusari, Jember District - Safitri, Nanda Rizki; Santika, Siska Dwi; Munawwaroh, Madinatul (META: Journal of Science and Technological Education, 2023)
The study focuses on the empowerment of Pakusari TPA educational tourism in Jember Regency, Indonesia. Waste management is a pressing issue worldwide, and the waste reduction process plays a crucial role in minimizing the amount of waste reaching the final disposal site. The research adopts a qualitative approach, utilizing survey techniques, interviews, field observations, and literature reviews to gather data. The findings reveal that the establishment of the Pakusari TPA educational tour was prompted by the increasing amount of waste and the need to educate the public about waste processing. The tour location, adjacent to the landfill, showcases creative waste conversions, such as statues made from discarded materials. Interviews with the TPA management indicate positive responses from local residents, schools sending students for educational visits, and a reduction in daily waste volume. The Pakusari TPA serves as an educational tourist attraction, promoting waste management practices and recycling initiatives. Through recycling, organic waste is converted into methane gas and animal feed, while inorganic waste is repurposed for pavement and artistic displays. Overall, the study highlights the benefits of the Pakusari TPA educational tourism in raising awareness, inspiring waste reduction, and fostering environmental preservation.